Job Scheduling Strategies for Parallel Processing 15th International Workshop, JSSPP 2010, Atlanta, GA, USA, April 23, 2010, Revised Selected Papers - Frachtenberg, Eitan; Schwiegelshohn, Uwe.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the revised papers of the 15th International Workshop on Job Scheduling Strategies for Parallel Processing, JSSPP 2010, which was held in Atlanta, GA, USA, in April 2010. The 12 revised papers presented were carefully reviewed and selected from 18 submissions. The papers show a prolific growth in the areas of applicability for parallel scheduling and discuss more recent problems and applications, such as virtualized environments, many-core processors, DNA sequencing, and hadoop.
Resource Provisioning in SLA-Based Cluster Computing -- An Advance Reservation-Based Co-allocation Algorithm for Distributed Computers and Network Bandwidth on QoS-Guaranteed Grids -- A Greedy Double Auction Mechanism for Grid Resource Allocation -- Risk Aware Overbooking for Commercial Grids -- The Gain of Resource Delegation in Distributed Computing Environments -- A Moldable Online Scheduling Algorithm and Its Application to Parallel Short Sequence Mapping -- Dynamic Proportional Share Scheduling in Hadoop -- The Importance of Complete Data Sets for Job Scheduling Simulations -- Hierarchical Scheduling of DAG Structured Computations on Manycore Processors with Dynamic Thread Grouping -- Multiplexing Low and High QoS Workloads in Virtual Environments -- Proposal and Evaluation of APIs for Utilizing Inter-Core Time Aggregation Scheduler -- Using Inaccurate Estimates Accurately.
Keywords: Computer science; Computer Communication Networks; Software engineering; Operating systems (Computers).; Computer software; Computer simulation; Computer Science; Software Engineering; Operating Systems; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering/Programming and Operating Systems; Simulation and Modeling